2021
DOI: 10.1080/14763141.2021.1877336
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and kinematic determinants of shuttlecock speed in the forehand jump smash performed by elite male Malaysian badminton players

Abstract: Badminton is the fastest racket sport in the world with smash speeds reaching over 111 m/s (400 kph). This study examined the forehand jump smash in badminton using synchronised force plates and full-body motion capture to quantify contributions to shuttlecock speed through correlations. Nineteen elite male Malaysian badminton players were recorded performing forehand jump smashes with the fastest, most accurate jump smash from each player analysed. The fastest smash by each participant was on average 97 m/s w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Badminton is a fast racket sport characterized by the ability to perform high-intensity and explosive movements such as lunges, jumps and overhead shuttlecock smashes interspersed with brief recovery periods [ 1 ]. Competitive success in badminton also depends on technical mastery, tactical shrewdness and mental toughness [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Badminton is a fast racket sport characterized by the ability to perform high-intensity and explosive movements such as lunges, jumps and overhead shuttlecock smashes interspersed with brief recovery periods [ 1 ]. Competitive success in badminton also depends on technical mastery, tactical shrewdness and mental toughness [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-five percent of the studies reviewed used inverse kinematics to obtain the force data at the joints of interest in order to investigate the indicators that lead to higher movement speed and performance [8,10,18,23,34,42,45,[49][50][51] and/or to examine the amount of forces incurred from the joints when executing the tasks from an injury risk perspective [23,41,42,45,59]. For example, [10] identified greater shoulder internal rotation moment as a strong predictor of higher racket head speed (r = 0.737); this was supported by [45] who found greater shoulder internal rotation moment in the skilled vs. novice players (p = 0.016). Ref.…”
Section: Type Of Biomechanical Analysis Approachesmentioning
confidence: 99%
“…Previous studies have reported peak angular velocities as high as 2594 • /s in volleyball jump spike [15], 2900 • /s in tennis serve [16], 7148 • /s in badminton jump smash [10], and 7200 • /s in baseball pitching [17,18]. These high angular velocities suggest shoulder internal rotation is important to speed development in overhead sporting motions, although methodological differences mean caution should be taken when comparing across studies on different sporting movements.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As for badminton players, our previous studies showed that training hours of per day, decreased trunk rotation and weak balance ability were risk factors for shoulder pain [11,12] . Although previous badminton studies adopted biomechanics to examine forehand overhead stroke motion [5,13,14] , no studies on the association of forehand overhead stroke motion phases and shoulder pain and injury were found. Additionally, video analysis has high reliability to evaluate sports motor skills, including phases of overhead motion [15,16] , however, such studies of badminton were scarce.…”
mentioning
confidence: 99%